L'Université McGill et la société québécoise francophone, 1951-1969 - Leduc, Bernard (Université de Montréal, 1999)
Keywords: Université McGill

Interkulturelle Landeskunde im Bereich des Deutschen als Fremdsprache an kanadischen Hochschulen: Dokumentation einer Fallstudie am Department of German Studies der McGill University, Montreal, Quebec, Kanada - Mollinger, Karin (Université McGill, 1996)
Keywords: Allemands; Université McGill

"The Big Ladies' Hotel": Gender, Residence, and Middle-Class Montreal: A Contextual Analysis of the Royal Victoria College, 1899-1931 - Miller, Deborah L. (Université McGill, 1998)
Keywords: Femmes; Royal Victoria College; Université McGill

Étude patrimoniale des sites et des bâtiments hospitaliers reliés à l'Université McGill - Lachapelle, Jacques; Bisson, Pierre-Richard (1997)
Keywords: Hôpital Général; Hôpitaux; Royal Victoria Hospital

George Heath MacDonald (Class of 1911): The Story of One Graduate from McGill University's School of Architecture - Johnson, Percy (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

Teaching the History of Architecture at McGill, 1896-1903 - Schoenauer, Norbert (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

The First Leaders of McGill's School of Architecture: Stewart Henbest Capper, Percy Nobbs, and Ramsay Traquair - Gournay, Isabelle (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Université McGill

James McGill of Montreal - Frost, Stanley Brice (McGill-Queen's University Press, 1995)
Keywords: McGill; James; Université McGill

McGill Medicine. Vol. 1 - The First Half Century, 1829-1885 - Hanaway, Joseph; Cruess, Richard L. (McGill-Queen's University Press, 1996)
Keywords: Médecine; Université McGill

Science and Engineering at McGill and Queen's Universities and the University of Toronto, 1880s to 1920s - Creet, Mario (Université Queen's, 1993)
Keywords: Ingénieurs; Université McGill

La physique à McGill entre 1920 et 1940: la réception de la mécanique quantique par une communauté scientifique périphérique - Gingras, Yves (Scientia Canadensis: Canadian Journal of the History of Science, Technology and Medicine / Scientia Canadensis : revue canadienne d'histoire des sciences, des techniques et de la médecine, 1991)
Keywords: Physique; Université McGill

'Archi-ettes' in Training: The Admission of Women to McGill's School of Architecture - Adams, Annmarie (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1996)
Number: 3
Keywords: Femmes; Université McGill

Émergence et évolution de la recherche en mathématiques au Québec, 1945-1984 - Foisy, Martine; Gingras, Yves (Société mathématique du Canada, 1945-1995. Vol. 1: Les mathématiques au Canada, 1995)
Keywords: Université McGill; Université de Montréal

L'institutionnalisation de la recherche en milieu universitaire et ses effets - Gingras, Yves (Sociologie et sociétés, 1991)
issued: 1991-21-00
Keywords: Université McGill; Université de Montréal

John William Dawson: Faith, Hope, and Science - Sheets-Pyenson, Susan (McGill-Queen's University Press, 1996)
Keywords: Dawson; William; Université McGill

Introduction - Keating, Peter; Keel, Othmar (Santé et société au Québec: XIXe-XXe siècle, 1995)
Keywords: Médecine; Université McGill; Université de Montréal

University Club de Montréal - Noppen, Luc (Les chemins de la mémoire. Monuments et sites historiques du Québec, 1991)
Keywords: Clubs; Patrimoine; Université McGill

Attractions, curiosités, carnaval d'hiver, expositions agricoles et industrielles: le loisir public à Montréal au XIXe siècle - Dufresne, Sylvie (Montréal au XIXe siècle. Des gens, des idées, des arts, une ville, 1990)
Keywords: Carnaval; Expositions; Université McGill

The Man in the Ivory Tower: F. Cyril James of McGill - Frost, Stanley Brice (McGill-Queen's University Press, 1991)
Keywords: James; F. Cyril; Université McGill

Carrie Derrick (1862-1941) and the Chair of Botany at McGill - Gillett, Margaret (Despite the Odds: Essays on Canadian Women and Science, 1990)
Keywords: Botanique; Derrick; Carrie; Université McGill

The Design of the Peter Redpath Museum at McGill University: the Genesis, Expression and Evolution of an Idea about Natural History - Bronson, Susan D. (Université de Montréal, 1992)
Keywords: Musées; Redpath (musée); Université McGill

The Design of the Peter Redpath Museum at McGill University: The Genesis, Expression, and Evolution of an Idea About Natural History - Bronson, Susan (Bulletin | Society for the Study of Architecture in Canada/Société pour l'étude de l'architecture au Canada, 1992)
Number: 3
Keywords: Musées; Redpath (musée); Université McGill

La réception des rayons X au Québec: radiographie des pratiques scientifiques - Gingras, Yves (A New Kind of Ray: the Radiological Sciences in Canada - les Sciences radiologiques au Canada, 1895-1995, 1995)
Keywords: Médecine; Physique; Technologie médicale; Université McGill

The Heart of the Matter: Maude E. Abbott, 1869-1940 - Gillett, Margaret (Despite the Odds. Essays on Canadian Women and Science, 1990)
Keywords: Abbott; Maude E.; Femmes; Médecine; Université McGill

Les hommes-relais de la bactériologie en territoire québécois et l’introduction de nouvelles pratiques diagnostiques et thérapeutiques (1890-1920) - Goulet, Denis; Keel, Othmar (Revue d'histoire de l'Amérique française, 1993)
Number: 3
Keywords: Hôpital Notre-Dame; Médecine; Université McGill; Université de Laval à Montréal; Université de Montréal

Getting a Job Done and Doing It Well: Dr. Blossom Wigdor, Psychologist and Gerontologist - Beaveridge, Janice (Despite The Odds: Essays on Canadian Women and Science, 1990)
Keywords: Femmes; Gérontologie; Psychologie; Université McGill; Wigdor; Blossom

The Gurds, the Montreal General and McGill: a family saga - Gurd, Fraser N. (General Store Publishing House, 1996)
Keywords: Hôpitaux; Montreal General Hospital; Médecine; Université McGill; École de médecine

La Crise d'octobre et le milieu universitaire montréalais - Bédard, Éric (Université de Montréal, 1997)
Keywords: Crise d'octobre; Front de Libération du Québec; Université McGill; Université Sir George Williams; Université de Montréal; Université du Québec à Montréal; Étudiants

A Study of the Garrison Families in Montreal and Quebec City, 1855-1865 - Duchesne, André (Université McGill, Département de géographie, 1990)
Keywords: Famille; Garnison

Understanding the Patterns of Language Use of Chinese Children in a Montreal Community School - Curdt-Christiansen, Xiao Lan (Université McGill, 1999)
Keywords: Chinois; Langue; Étudiants

Ukrainian Community Life in Montreal: Social Planning Implications - Tokar, Ann M. (Université McGill, 1992)
Keywords: Ukrainiens

Transforming the Ideal: Visions and Revisions of Housing in a French-Canadian Community, 1942-1995 - Gilliland, Jason A. (Université McGill, 1996)
Keywords: Cité-Jardin du tricentenaire; Logement

The Saint Patrick's Society of Montreal: Ethno-Religious Realignment in a Nineteenth-Century National Society - James, Kevin (Université McGill, 1997)
Keywords: Irlandais

The Education of Italians in Montreal, 1895 to 1960 - Gadler, Yves Carmelo Luciano (Université McGill, 1994)
Keywords: Italiens

Safeguarding Mother Tamil in Multicultural Quebec: Sri Lankan Legends, Canadian Myths, and the Politics of Culture - Brunger, Fern (Université McGill, 1994)
Keywords: Sri Lankais

Renegotiating Home and Identity: Experiences of Gujarati Immigrant Women in Suburban Montreal - Nair, Roopa (Université McGill, 1998)
Keywords: Femmes; Indiens

L'insegnamento dell'italiano a Montreal verso il Duemila. Insegnamento e apprendimento al livello post-secondario in un contesto plurilingue - Picciano, Giovanna A. (Université McGill, 1997)
Keywords: Italiens; Langue

Die Geschichte des deutschsprachigen Theaters in Montreal von seinen Anfängen 1953 bis 1997 - Kremer, Johanna (Université McGill, 1998)
Keywords: Allemands; Théâtre

Des écoles à rendre communautaires - Lamarre, Jules (Université McGill, 1991)

Suspended Conversations: Private Photographic Albums in the Public Collection of the McCord Museum of Canadian History - Langford, Martha (Université McGill, 1997)
Keywords: Musée McCord; Musées; Photographie

Poésie et discours poétique au Canada français (1889-1909) - Campeau, Sylvain (Université McGill, 1999)
Keywords: Poésie

A History of Playwrights' Workshop Montreal, 1963-1988 - Curtis, Ron (Université McGill, 1991)
Keywords: Atelier de dramaturgie de Montréal (Playwrights' Workshop Montréal); Théâtre

Troubling Below: Rethinking Subcultural Theory - Stahl, Geoff (Université McGill, 1998)
Keywords: Musique

Word, Sound and Power: Rastafari and Conceptions of Musical Meaning in Roots Reggae Music - Macaulay, David E. (Université McGill, 1993)
Keywords: Musique

Modular Prefabrication versus Conventional Construction as a Cost Effective Alternative for the Construction of Single Family Detached Housing in the Montreal Area - Wiedemann, Stefan J. (Université McGill, 1990)
Keywords: Logement

La relation entre l'évolution du salaire réel et de l'emploi: Montréal, 1963-1982 - Dagenais, Vincent (Université McGill, 1990)

Destination, Housing and Quality of Life in the Migrant Experience from Larino (Molise, Italy) to Milano and Montreal - Fainella, John G. (Université McGill, 1996)
Keywords: Italiens; Logement

Working for Family, Nation and God: Paternalism and the Dupuis Frères Department Store, Montreal, 1926-1952 - Matthews, Mary Catherine (Université McGill, 1997)
Keywords: Commerce de détail; Dupuis Frères; Magasins; Travail

Domesticating Parks and Mastering Playgrounds: Sexuality, Power and Place in Montreal, 1870-1930 - Schmidt, Sarah (Université McGill, 1997)
Keywords: Délinquance; Mont-Royal (parc); Parcs; Places publiques

Residential Mobility in Montreal, 1861-1901 - Gilliland, Jason A. (Université McGill, 1993)
Keywords: Famille; Logement; Mobilité résidentielle

The Cholera Epidemic of 1832: State Formation and the Origins of the Montreal Board of Health - Sendzik, Walter (Université McGill, 1997)
Keywords: Choléra; Épidémies

Narratives and Identities in the Saint Lawrence Valley, 1667-1720 - Gray, Linda Breuer (Université McGill, 1999)

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires

In Quest of Emotional Gratification and Cognitive Consonance: Organized Labour and Québec Separatist Nationalism, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1997)
Keywords: Nationalisme; Travail

W.D. Lighthall: Sometime Confederation Poet, Sometime Urban Reformer - Wright, Donald A. (Université McGill, 1991)
Keywords: Lighthall; William Douw; Réformistes; Écrivains

The Confédération des syndicats nationaux, the Idea of Independence, and the Sovereigntist Movement, 1960-1980 - Güntzel, Ralph Peter (Université McGill, 1991)
Keywords: Confédération des syndicats nationaux; Nationalisme

La motorisation ou "La rançon du progrès". Tramways, véhicules-moteurs et circulation (Montréal, 1900-1930) - Veilleux, Denis (Université McGill, 1998)
Keywords: Automobile; Tramways; Transport en commun

Long-Term Results of User Participation in Housing Rehabilitation: The Community Design Workshop in Pointe St. Charles - You, Danhui (Université McGill, 1998)
Keywords: Logement; Pointe-Saint-Charles

Les aubergistes et les cabaretiers à Montréal en 1700 - Poliquin, Marie-Claude (Université McGill, 1996)
Keywords: Auberges

Menstruation Goes Public: Aspects of Women's Menstrual Experience in Montreal, 1920-1975 - Armeni, Elizabeth (Université McGill, 1996)
Keywords: Femmes

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

St. Lawrence Blvd. as "Third City": Place, Gender and Difference along Montréal's "Main" - Podmore, Julie (Université McGill, 1999)
Keywords: Rues; Saint-Laurent (rue)

Women in Montreal during Three Wars: an Examination of Gender, Nationalism and Colonialism - Pickles, Katie (Université McGill, 1996)
Keywords: Femmes; Guerre; Nationalisme

Women and Political Participation: the Montreal Citizens Movement, 1974-1989 - Van der Veen, Paula Louise (Université McGill, 1990)
Keywords: Femmes; Rassemblement des citoyens et citoyennes de Montréal

Salubrious Settings and Fortunate Families: The Making of the Golden Square Mile, 1840-1895 - MacLeod, Roderick (Université McGill, 1998)
Keywords: Anglophones; Golden Square Mile; Protestants; Quartiers

The Kahnawake Iroquois and the Lower-Canadian Rebellions, 1837-1838 - Sossoyan, Matthieu (Université McGill, 1999)
Keywords: Autochtones; Iroquois; Rébellions

Images and Reality of Fatherhood: a Case Study of Montreal's Protestant Middle Class, 1870-1914 - Fish, Cynthia (Université McGill, 1992)
Keywords: Famille; Protestants

City at War: The Effects of the Second World War on Verdun, Québec - Durflinger, Serge Marc (Université McGill, 1997)
Keywords: Guerre; Quartiers; Verdun

A Recreational Hinterland Comparison between Montréal and Québec City - Secondi, Bruno (Université McGill, 1990)

Housing of Female Single-Parent Families with Special Reference to Point St. Charles - Bourianova, Ioulia (Université McGill, 1996)
Keywords: Femmes; Logement; Pointe-Saint-Charles; Quartiers

The Evolution of Montreal’s Cemetery Space from 1642 to the Present - Mappin, Charles (Université McGill, 1995)
Keywords: Cimetières

Madame James McGill (1747-1818): Marie-Charlotte Guillimin, ou, La vie d'une femme mondaine à Montréal au dix-huitième siècle - Tanguay, Lynda (Université McGill, 1993)
Keywords: Bourgeoisie; McGill; James

The Law of Servants and the Servants of the Law: Judicial Regulation of Labour Relations in Montreal, 1830-1845 - Pilarczyk, Ian C. (Université McGill, 1997)
Keywords: Droit; Travail

Socio-Cultural Factors Affecting the Language Learning Experiences of South Asian Female Immigrants - Steinbach, Marilyn (Université McGill, 1998)
Keywords: Bengalis; Femmes; Indiens; Langue; Pakistanais; Sri Lankais

Rethinking Juvenile Prostitution: Insights from Youths on the Street - Morris, Jason (Université McGill, 1999)
Keywords: Enfants; Prostitution

Loft Conversions in a Local Context: The Case of Inner City Montreal - Podmore, Julie (Université McGill, 1994)
Keywords: Logement

Community Response to Environmental Change: A Case Study of Montreal's West Island 1981-1991 - Adams, Jennifer (Université McGill, 1992)
Keywords: Quartiers; West Island

Mutual Aid Networks in Two Feminist Housing Co-Operatives in Montreal - Yasmeen, Gisèle (Université McGill, 1991)
Keywords: Féminisme; Logement

Uncompleted Condominiums: A Strategy for Cost Reduction in Montreal Housing - Kowalska, Danuta (Université McGill, 1991)
Keywords: Logement

The Restructuring of the Montreal Tourism Industry: A Sectoral Analysis - Pohlmann, Corinne (Université McGill, 1994)
Keywords: Tourisme

Representing Twentieth Century Canadian colonial Identity: the Imperial Order Daughters of the Empire (IODE) - Pickles, Catherine Gillian (Université McGill, 1996)
Keywords: Britanniques; Femmes

The Attitudes of Students of Greek Origin in a French-Language Learning Situation in a Québec Secondary School - Waite, Richard (Université McGill, 1991)
Keywords: Grecs; Langue; Étudiants

Identity, Place and Community: A Latin American Locale in Montreal - Occhipinti, Joseph (Université McGill, 1996)
Keywords: Latino-Américains

Formalization in a Social Movement Organization: Cooptation or Survival? A Case Study of a Feminist Shelter for Battered Women - Nordquist, Karen L. (Université McGill, 1998)
Keywords: Femmes; Groupes populaires

Montreal Association for the Blind: User Satisfaction Survey - McGraw, Cathy (Université McGill, 1997)

Labyrinth: Cinema, Myth and Nation at Expo 67 - Whitney, Allison (Université McGill, 1999)
Keywords: Cinéma; Expositions

The Cemetery and Cultural Memory: Montreal Region, 1860 to 1900 - Watkins, Meredith G. (Université McGill, 1999)
Keywords: Cimetières

A Synoptic Climatology of Ground-Level Ozone for Montreal, Quebec - Stephens, Kate (Université McGill, 1995)
Keywords: Climat

A Synoptic Climatology of Montreal Precipitation - Fischer, Alexander P. (Université McGill, 1998)
Keywords: Climat

Small Living Spaces: A Study of Space Management in Wartime Homes in Montreal - Pantelopoulos, Maria D. (Université McGill, 1993)
Keywords: Logement

The Evolution of Prefabricated Interior Components for Post-Occupancy Modification - Ou, Yangli (Université McGill, 1999)

Sky's the Limit: The Operations, Renovations and Implications of a Montréal Gay Bar - Allan, James (Université McGill, 1997)
Keywords: Alcool

Les fonctions politiques du centre culturel: La Place des Arts et la Révolution tranquille - Illien, Gildas (Université McGill, 1995)
Keywords: Place des Arts; Places publiques

Human Scale in the Urban Design of Montreal Residential Developments - Lucic, Katija (Université McGill, 1995)
Keywords: Anjou; Banlieue; Centre-sud (quartier); Quartiers; Rues; Squares

Joseph Gould and the Montreal Mendelssohn Choir - Rice, Kelly Stanley (Université McGill, 1991)
Keywords: Musique

Privacy in Row Houses of Montreal - Rahbar, Mehrdad (Université McGill, 1996)
Keywords: Logement

Shifting Cultures of Recycled Style: A History of Second-Hand Clothing Markets in Montreal - Diggins, Kimberly A. (Université McGill, 1998)
Keywords: Vêtements

The Rebirth of the Shophouse in the Modern Age with a Special Reference to Montreal - Xu, Ti (Université McGill, 1998)
Keywords: Logement

Criminal Women and Bad Girls: Regulation and Punishment in Montreal, 1890-1930 - Myers, Tamara (Université McGill, 1996)
Keywords: Criminalité; Délinquance; Femmes; Prisons

Coping with the HIV and AIDS Epidemic in HIV Seronegative Gay Males in Montreal - Watson, Scott C. A. (Université McGill, 1999)
Keywords: Épidémies

Broadway North: Musical Theatre in Montreal in the 1920s - Charpentier, Marc (Université McGill, 1999)
Keywords: Musique; Théâtre

Authoritarianism, Constitutionalism and the Special Council of Lower Canada, 1838-1841 - Watt, Steven (Université McGill, 1998)
Keywords: Association constitutionnelle de Montréal (MCA); Loyalistes; Rébellions

A Sense of Belonging: Pre-Liberation Space, Symbolics, and Leadership in Gay Montreal - Higgins, Ross (Université McGill, 1997)

A Neighborhood that Empowers Women: In Search of Housing Sustainability - Insaf, Zeenat S. (Université McGill, 1999)
Keywords: Femmes; Logement

Constructing Italian Ethnicity: A Comparative Study of Two Italian Language Newspapers in Australia and Canada, 1947-1957 - Iuliano, Susanna (Université McGill, 1994)
Keywords: Italiens

Columns on the March: Montreal Newspapers Interpret the Spanish Civil War, 1936-1939 - Charpentier, Marc (Université McGill, 1992)
Keywords: Canada (Le); Clarté; Devoir (Le); Illustration Nouvelle (L'); Jour (Le); Journalistes; McGill Daily; Monde ouvrier (Le); Montreal Standard; Montreal Star; Montréal-Matin; Unité (L')

Coming into Site: Identity, Community and the Production of Gay Space in Montréal - Doyle, Vincent André (Université McGill, 1996)

Chinese-Canadian Women in Montreal: Case Studies in the Importance of Education - Li, Sharon (Université McGill, 1995)
Keywords: Chinois; Femmes

Imagining Ethnicity. The Role of the Montreal Bangladeshi Press in Ethnic Cohesion - Ahmed, Shameem (Université McGill, 1997)
Keywords: Bengalis

The Adjustment of Israeli Immigrant Students in Montreal - Gutstadt, Pnina (Université McGill, 1996)
Keywords: Israéliens; Juifs; Étudiants

Captives in Canada, 1744-1763 - Gray, Colleen (Université McGill, 1993)
Keywords: Autochtones; Britanniques; Captifs

Languages in Contact: Error Analysis of Italian Childrens' Compositions in a Multilingual Context - Samperi Mangan, Jacqueline (Université McGill, 1991)
Keywords: Enfants; Italiens; Langue

Jewish Supplementary Schooling in Montreal in the Latter Part of the Twentieth Century - Segal, Sima (Université McGill, 1991)
Keywords: Bureau des écoles protestantes; Juifs; Langue

Intra-Ethnic Differences of the Perceptions of Aged Italian Women in Receiving Care - Bonar, Rita Aguzzi (Université McGill, 1993)
Keywords: Femmes; Italiens

Hometown and Family Ties: The Lebanese-Syrians of Montreal, 1905-1950 - Moser, Diane (Université McGill, 1990)
Keywords: Libanais; Syriens

Gender, Race, and Power: the Chinese in Canada, 1920-1950 - Huang, Belinda (Université McGill, 1998)
Keywords: Chinois

Family, Paesani and Networks: Politics and Economy of Montreal Italians - Aramaki, Michiko (Université McGill, 1994)
Keywords: Italiens

Industry and Space: the Making of Montreal's Industrial Geography, 1850-1918 - Lewis, Robert D. (Université McGill, 1992)
Keywords: Banlieue; Quartiers; Saint-Henri; Sainte-Anne

Integrating Islam: A Muslim School in Montreal - Kelly, Patricia (Université McGill, 1997)
Keywords: Musulmans

Housing the Grey Nuns: Power, Religion and Women in fin-de-siècle Montréal - Martin, Tania Marie (Université McGill, 1995)
Keywords: Communautés religieuses; Couvents; Soeurs Grises

The Role of the Parish in Fostering Irish-Catholic Identity in Nineteenth-Century Montreal - Trigger, Rosalyn (Université McGill, 1997)
Keywords: Irlandais; Notre-Dame (paroisse)

Faubourg des Récollets: projet de mise en valeur - Malo, Pierre (Université McGill, 1991)
Keywords: Faubourgs

Class, Culture, Family and the Law: Wife to Widow in Nineteenth-Century Quebec - Bradbury, Bettina (Programme d'études sur le Québec de l'Université McGill, 1997)
Keywords: Femmes; Mariage; Veuvage